Down the memory lane Revisiting the 1972 Hwange Colliary Kamandama Disaster - Farai Ncube (Cite Factor, 2023)
On the morning of 6 June 1972, 427 coal miners perished in a suspected methane gas explosion in Hwange Colliery Kamandama Shaft. On that fateful day Miners from South Africa, Angola, Zambia, Malawi, and Costa Rica met their untimely death at the number two mine. This has been the worst mining disaster ever in Zimbabwe’s history, which hampered sustainable development. Through content analysis, questionnaires and interviews research findings suggest that the suspected causes of the accident were, blown out Shots, Welding and the Collapse of Panels, sabotage and diesel fuel fires. To ensure effective sustainable development the company embarked on a massive campaign to curb any occupational hazards mainly through observing contraband rules, ISO certification, and setting proto teams, sub-contracting rock specialists, maintaining a well informed safety department. The paper recommends, the use of person wearable methane control monitors, maximum stone dusting, methane drainage, and the elimination of igniting sources.